2021
DOI: 10.3390/ijms221910596
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Endothelial Leptin Signaling Increases Vascular Adrenergic Reactivity in a Mouse Model of Congenital Generalized Lipodystrophy

Abstract: The adipokine leptin, which is best-known for its role in the control of metabolic function, is also a master regulator of cardiovascular function. While leptin has been approved for the treatment of metabolic disorders in patients with congenital generalized lipodystrophy (CGL), the effects of chronic leptin deficiency and the treatment on vascular contractility remain unknown. Herein, we investigated the effects of leptin deficiency and treatment (0.3 mg/day/7 days) on aortic contractility in male Berardinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Indeed, we showed that while T1D and PFKFB3 overexpression selectively increased the expression of Nox1 and its co-activator NoxA1 in ECs, pharmacological and genetic inhibition of Nox1 restored endothelial function. These findings are consistent with previous work by our group and others highlighting a key role for high endothelial Nox1 expression in reduced NO bioavailability and endothelial dysfunction 24,35,36 but also with reports suggesting a link between glycolysis and Nox-derived ROS. 28 Remarkably, we provided evidence supporting a role for lactate, the end product of glycolysis, in Nox1 upregulation.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we showed that while T1D and PFKFB3 overexpression selectively increased the expression of Nox1 and its co-activator NoxA1 in ECs, pharmacological and genetic inhibition of Nox1 restored endothelial function. These findings are consistent with previous work by our group and others highlighting a key role for high endothelial Nox1 expression in reduced NO bioavailability and endothelial dysfunction 24,35,36 but also with reports suggesting a link between glycolysis and Nox-derived ROS. 28 Remarkably, we provided evidence supporting a role for lactate, the end product of glycolysis, in Nox1 upregulation.…”
Section: Discussionsupporting
confidence: 93%
“…The mechanism(s) whereby leptin induces endothelial damage in females may be an indirect mechanism involving the renin-angiotensin-aldosterone system (RAAS). Previous studies show that leptin promotes the development of hypertension and endothelial dysfunction in obese males via increased sympathetic activation; however, these sympathetic nervous system mechanisms are not observed in females [18,[37][38][39]. Aldosterone is a critical regulator of blood pressure and vascular tone.…”
Section: Leptin-induced Endothelial Dysfunction Is Sex-dependentmentioning
confidence: 99%
“…Endothelium intact aortic rings were mounted in a wire myograph (Danysh MyoTechnology) for isometric tension recordings with PowerLab software (AD Instruments) as described [18][19][20][21] . Briefly, rings (2mm) were placed in tissue baths containing warmed (37 °C), aerated (95% O2, 5% CO2) Krebs Henseleit Solution: (in mM: 130 NaCl, 4.7 KCl, 1.17 MgSO4, 0.03 EDTA, 1.6 CaCl 2, 14.9 NaHCO3, 1.18 KH2PO4, and 5.5 glucose) and after 30 min of stabilization, arteries were incubated with KCl (60mM) to test the sample viability.…”
Section: Vascular Reactivitymentioning
confidence: 99%